"They are not satisfied until they see our blood": Syndemic HIV risks for trans women in urban Haiti. Issue 4 (2nd October 2021) - Joshi, Manisha; J. Rahill, Guitele; Carrington, Cherelle; Mabie, Alexander; Salinas-Miranda, Abraham; Thomas, Nicholas; Morales, Amanda; Grippo, Lucy; Grey, Amanda
Abstract: The contribution of gender identity, neighborhood characteristics, contextual norms, and socio-political factors to the biopsychosocial health of non-heteronormative persons in low- and middle-income countries (LMICs) is understudied. Using syndemic theory, we conducted two focus groups (FGs) of 16 non-heteronormative individuals in Haiti's urban Cité Soleil neighborhood. Eight individuals participated in each FG. ATLAS.ti facilitated thematic content analysis of transcripts. Results indicate that disparity conditions in Cité Soleil (extreme poverty, gang violence, easy access of weapons by criminals, lack of law enforcement, and a 3.6% Human Immunodeficiency Virus [HIV] rate) facilitate a syndemic of substance abuse and non-partner sexual violence. These interact adversely with gender expression, transphobia, transmisogyny, cissexism, lack of confidential HIV testing, and hostilities from religious groups to increase participants' risks of coercive non-partner sexual violence by groups of inebriated men. Injuries from sexual violence, limited access to confidential HIV testing, and inaccurate HIV knowledge heighten HIV risk and anxiety. Haiti's negative human rights record, 2.2% HIV prevalence, and cultural norms that devalue women are syndemic pathways that perpetuate or worsen disparity conditions and health risks, particularly for trans women. It is a moral, ethical, public health, and social justice mandate to address HIV prevention and mental health promotion for Haitian trans women.